The Effect of Fenugreek Paste on Physical Quality and Organoleptic Quality Meatballs Made From Chicken Meat - Nur Laila; Peni Patriani; Ade Trisna (Jurnal Peternakan Integratif, 2023)
Meatballs is a processed meat product and one of Indonesia's favourite culinary delights. This study aims to determine the effect of fenugreek paste on the physical and organoleptic quality of meatballs made from chicken meat. The research was conducted in June-July 2023 at the Research and Technology Laboratory, Faculty of Agriculture, and Animal Production Laboratory, Faculty of Agriculture, University of No Sumatra. The design used in this study was RAL (Completely Randomised Design) with 4 treatments, namely P0 = 0%, P1 = 5%, P2 = 10%, P315%, and 5 replications. The parameters in this study were physical quality tests, namely meatball pH and cooking loss, and organoleptic tests of color, aroma, taste, and tenderness. The results showed that 5%, 10%, 15% fenugreek paste had a very significant effect (P<0.01) on physical quality and organoleptic quality. The higher the percentage of fenugreek paste used in meatballs, the higher the physical and organoleptic quality of meatballs In conclusion of this study is that fenugreek is good to add to get quality meatballs